Molecular dynamics simulation and thermo-mechanical characterization for optimization of three-phase epoxy/TiO2/SiO2 nano-composites - Akbar Takari (Elsevier, 2021)
In this research, experimental and theoretical method are used to improve and optimized the thermo-mechanical properties of hybrid Epoxy/TiO2/SiO2 nano-Composites. For investigation of the influence of weight percentage of Silica toward Titana in TiO2–SiO2 hybrid nanoparticles on tensile properties of epoxy, the composite was optimized by surface methodology. Thirteen experiments were designed by using design expert commercial software totally. The TiO2–SiO2 hybrid nanoparticles were synthesized by sol-gel method. Then, epoxy/TiO2–SiO2 nanocomposites were prepared by direct mixing method. Four factors as elongation at break (EAB), yield strength (σy), ultimate strength (σu) and elastic modulus (E) were investigated by using tensile test device. The optimization results showed that the best (EAB), (σy), (σu) and (E) outcomes are 29.3, 17.72, 17.43 and 4.34% respectively with 14.64% weight percent of Silica in total amount of TiO2–SiO2 0.73% hybrid nanoparticles. In order to investigate the chemical and thermo-mechanical properties of nanocomposite as tensile tests, TGA, XRD, FT-IR, SEM, EDX and DRS analysis were performed. In addition, due to the high reliability in predicting the reaction among different materials and comparing with the results of experimental work, which is based on polymer-nanoparticle interaction energy, molecular dynamics simulation (MD) were used. The simulations were performed by using materials studio (MS) software. The numerical and analytical results show that the presence of small amount of Silica beside Titanium creates a strong interaction between fillers and epoxy resin.